Personal Essay Writing of Parveen Tariq: A Critical Study - Alvi, Qamar Abbas; Sindhu, Aqsa Naseem; Majeed, Alia (sourcecoder, 2023)
Term Personal essay is used for such kind of writing that was started by French writer Michel de Montaigne and named Essai. In English it is called Personal or light essay while in Urdu it is called Inshaiya. The earliest traces of Inshaiya in Urdu can be found in the works of Mulla Wajhi's SUBRUS, the essays of Mir Nasir Ali and Sir Syed Ahmad Khan, letters of Mirza Asad Ullah Khan Ghalib or the short stories of Sajjad Haider Yaldarim. But as a genre of literature Dr. Wazir Agha and his friends (Anwar sadid, Mushtaq Qamar and Jameel Azar) performed it in the latter half of the twentieth century. Some women also played a fundamental role in promotion of urdu Inshaye, among which Parveen Tariq is the foremost.